Species of Prioninae, Parandrinae, Lepturinae (Insecta, Coleoptera, Cerambycidae) and Disteniidae (Insecta, Coleoptera) from east Paraná State (Brazil), with three new geographic distribution records - Barros, Rafael C. De; Fonseca, Mailson G. Da; de Arvarenga Julio, Carlos E. (Zootaxa, 2018)
A list of species of the Prioninae, Parandrinae and Lepturinae (Cerambycidae) and Disteniidae sampled in the Iguaçu National Park (PNI) from March 2012 to December 2015 using different collection methods, is presented. Twenty species were recorded, all of which are registered for the first time for the PNI, including three Parandrinae species represent new distribution records for the state of Paraná. Details of distribution, the material examined and an illustration are given for each species.